FORMATION OF POTENTIAL HETEROTIC GROUPS OF MAIZE INBRED LINES USING VARIATION AT SIMPLE SEQUENCE REPEAT LOCI - Neyaz R. Mustafa; Sakar A. Kakarash; Namam B. Ismael; Sebar D. Abdulazeez (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to identification of certain crosses to produce hybrids with higher performance per se can be aided by the determination of simple sequence repeats (SSR), which can improve our understanding of the genetic divergence of maize lines and their classification into different heterotic groups. Variability for each locus was measured using the polymorphism information content (PIC), with an average of 0.55, suggesting that the markers were highly informative. Analysis of the molecular variance (AMOVA) indicated higher divergence among the maize lines, suggesting the existence of different groups. The unweighted pair group method with arithmetic mean analysis (UPGMA) and the three-dimensional principal coordinate analysis (PCoA) revealed seven heterotic groups. Therefore, knowledge on the genetic diversity distribution in these maize inbred lines is essential to determine strategies to exploit heterosis in breeding programs in future studies.